The genus Weissella: taxonomy, ecology and biotechnological potential - Fusco, Vincenzina; Quero, Grazia M.; Cho, Gyu-Sung; Kabisch, Jan; Meske, Diana; Neve, Horst; Bockelmann, Wilhelm; Franz, Charles M. A. P. (Frontiers in Microbiology, 2015)
Bacteria assigned to the genus Weissella are Gram-positive, catalase-negative, non-endospore forming cells with coccoid or rod-shaped morphology (Collins et al., 1993; Björkroth et al., 2009, 2014) and belong to the group of bacteria generally known as lactic acid bacteria. Phylogenetically, the Weissella belong to the Firmicutes, class Bacilli, order Lactobacillales and family Leuconostocaceae (Collins et al., 1993). They are obligately heterofermentative, producing CO2 from carbohydrate metabolism with either d(−)-, or a mixture of d(−)- and l(+)- lactic acid and acetic acid as major end products from sugar metabolism. To date, there are 19 validly described Weissella species known. Weissella spp. have been isolated from and occur in a wide range of habitats, e.g., on the skin and in the milk and feces of animals, from saliva, breast milk, feces and vagina of humans, from plants and vegetables, as well as from a variety of fermented foods such as European sourdoughs and Asian and African traditional fermented foods. Thus, apart from a perceived technical role of certain Weissella species involved in such traditional fermentations, specific Weissella strains are also receiving attention as potential probiotics, and strain development of particularly W. cibaria strains is receiving attention because of their high probiotic potential for controlling periodontal disease. Moreover, W. confusa and W. cibaria strains are known to produce copius amounts of novel, non-digestible oligosaccharides and extracellular polysaccharides, mainly dextran. These polymers are receiving increased attention for their potential application as prebiotics and for a wide range of industrial applications, predominantly for bakeries and for the production of cereal-based fermented functional beverages. On the detrimental side, strains of certain Weissella species, e.g., of W. viridescens, W. cibaria and W. confusa, are known as opportunistic pathogens involved in human infections while strains of W. ceti have been recently recongnized as etiological agent of “weissellosis,” which is a disease affecting farmed rainbow trouts. Bacteria belonging to this species thus are important both from a technological, as well as from a medical point of view, and both aspects should be taken into account in any envisaged biotechnological applications.